2019
DOI: 10.1177/1074248419841632
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Humoral Factors in Remote Preconditioning of the Heart

Abstract: A humoral mechanism of cardioprotection by remote ischemic preconditioning (RIP) has been clearly demonstrated in various models of ischemia–reperfusion including upper and lower extremities, liver, and the mesenteric and renal arteries. A wide range of humoral factors for RIP have been proposed including hydrophobic peptides, opioid peptides, adenosine, prostanoids, endovanilloids, endocannabinoids, calcitonin gene-related peptide, leukotrienes, noradrenaline, adrenomedullin, erythropoietin, apolipoprotein, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 173 publications
0
21
0
4
Order By: Relevance
“…It is known that hemeoxygenase-1 (HO-1) promotes an increase in cardiac tolerance to ischemia/reperfusion. 151 It has been established the stimulation of peroxisome proliferator-activated receptor γ (PPARγ) increases myocardial resistance to ischemia/reperfusion. 159 It was shown that CNP induced activation of HO-1 expression in HUVECs.…”
Section: Potential Mechanisms Underlying the Infarct-reducing And Antmentioning
confidence: 99%
See 4 more Smart Citations
“…It is known that hemeoxygenase-1 (HO-1) promotes an increase in cardiac tolerance to ischemia/reperfusion. 151 It has been established the stimulation of peroxisome proliferator-activated receptor γ (PPARγ) increases myocardial resistance to ischemia/reperfusion. 159 It was shown that CNP induced activation of HO-1 expression in HUVECs.…”
Section: Potential Mechanisms Underlying the Infarct-reducing And Antmentioning
confidence: 99%
“…It is known that transcription factors are involved in the cardioprotective effect of pre- and postconditioning. 105,151 This is primarily signal transducer and activator of transcription (STAT) and nuclear factor kappa B (NFκB). 151 There are no evince on involvement STAT in the infarct-reducing effect of natriuretic peptides.…”
Section: Potential Mechanisms Underlying the Infarct-reducing And Antmentioning
confidence: 99%
See 3 more Smart Citations